Casa, espaço de acolhida e libertação para as primeiras comunidades cristãs - Bernardino, Orides (2011)
A home is not only a family shelter, but also the "space for socialization and sociability; for religiosity; for health care; for food reproduction". It is in the home environment "that the first human feelings such as intimacy, cooperation, habitus reproduction and family habits are developed, built and socialized". In the New Testament, the home represents a feeling that goes beyond a house or family reference, being filled up with historical and socio-economic associations, in partial continuity with the Old Testament. This paper tries to understand the function of the home and its importance for the structuring of the Christian mission as a space of welcoming, communion, liberation and inclusion, an important space for new communitarian and evangelical relationships having a transforming potential, where the family and the community can get together. The approach is made mainly taking into consideration Jesus' practices and those of primitive communities, according to the Act of the Apostles.